2011
DOI: 10.4161/cib.4.3.14886
|View full text |Cite
|
Sign up to set email alerts
|

N-Cadherin regulates radial glial fiber-dependent migration of cortical locomoting neurons

Abstract: During cerebral cortical development, post-mitotic neurons exhibit a multi-step migration. The locomotion mode covers most of the neuronal migration path. Although for many decades, locomoting neurons have been known to migrate along radial glial fibers, how the cortical locomoting neurons attach to and migrate along radial glial fibers was largely unknown. We recently reported that N-cadherin is required for cortical neuronal migration in vivo. Knockdown or dominant negative inhibition of N-cadherin results i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
72
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 74 publications
(76 citation statements)
references
References 28 publications
4
72
0
Order By: Relevance
“…S5 A-E), whereas overexpression of N-cadherin at a higher concentration (5.0 mg/mL) of the expression plasmid affected neuronal migration (Fig. S5 F-J), as reported previously (34). These results suggest that appropriate regulation, but not persistent increase, of the adhesive forces mediated by N-cadherin is necessary for the cortical neurons to settle in their proper positions eventually.…”
Section: Resultssupporting
confidence: 68%
“…S5 A-E), whereas overexpression of N-cadherin at a higher concentration (5.0 mg/mL) of the expression plasmid affected neuronal migration (Fig. S5 F-J), as reported previously (34). These results suggest that appropriate regulation, but not persistent increase, of the adhesive forces mediated by N-cadherin is necessary for the cortical neurons to settle in their proper positions eventually.…”
Section: Resultssupporting
confidence: 68%
“…1H), N-cadherin junctions on the surface of neighboring cells serve as a migration track. This N-cadherin junction dependent cell movement is also observed in cortical neuronal locomotion along radial glial fibers (Shikanai et al, 2011). Previous studies have shown that cells exert similar magnitudes of traction forces through N-cadherin junctions as focal adhesions (Ganz et al, 2006), suggesting that N-cadherin junctions are not passive contacts that maintain multicellular integrity, but rather act as an active participant of cell migration.…”
Section: Discussionmentioning
confidence: 75%
“…We have previously reported that Rab5-dependent endocytosis is required for several steps of neuronal migration, including the radial fiber-dependent locomotion mode Shikanai et al, 2011). However, in a series of these experiments, Rab5-shRNAs were expressed prior to the transition to the locomotion mode.…”
Section: Discussionmentioning
confidence: 99%